Chroogomphus gracilis (Gomphidiaceae, Boletales), a new species with mycocultural relevance in a Nahua-origin community in Central Mexico, and validation of four names of Boletes - Ayala-Vásquez, Olivia; Pinzón, Juan Pablo; Carrasco, Soledad Balbuena; Ávila-Caballero, Luz Patricia; Martínez-Reyes, Magdalena; Pérez-Moreno, Jesús (Phytotaxa, 2026)
Chroogomphus gracilis sp. nov. is described from Mexico, occurring in pine-oak mixed forests on the slopes of the Popocatépetl volcano. The species is characterized and documented based on both morphological features and molecular data. Phylogenetic analyses were performed using DNA sequences from the nuclear ribosomal internal transcribed spacer (nrITS) region. Comprehensive descriptions and photographic documentation of the new species are provided. C. gracilis is consumed by members of the local Nahua community of San Pedro Nexapa, state of Mexico, and commercialized in local markets located in the eastern part of the State of Mexico. Additionally, four bolete species described from Mexico in 2023 are here validated, as their protologues did not initially satisfy the stipulations of Articles F.5.1 and 40.7 of the International Code of Nomenclature for Algae, Fungi, and Plants.